Childhood borderline lepromatous leprosy - Susanto, Martin; Hutahaean, Grace Dumamawarni; Napitupulu, Tiopan; Siahaan, Andre Marolop Pangihutan (Indonesian Pediatric Society, 2024)
Leprosy (Morbus Hansen) is a chronic, severe infectious disease caused by the Mycobacterium leprae that mostly affects the skin, mucosa, eyes, and nerves. Despite the availability of effective treatment, leprosy has become a major public health problem in many developing countries.